"The Art or Mystery of Physick" – Asante Medicinal Plants and the Western Ordering of Botanical Knowledge. (5th August 2016) - McCaskie, Tom C.
Abstract: This paper deals with aspects of the still relatively neglected history of African medicinal plants. The core of the paper is a discussion in tabular form of the plants collected in the West African forest kingdom of Asante in 1817 by Henry Tedlie, a member of the well known English mission led by Thomas Bowdich. More generally, the paper considers episodes in the accumulation of Akan, Asante, and African plant specimens by Europeans, and the eventual classification of these in a western authorized botanical taxonomy that is now in worldwide use. The gathering of potentially medicinal plants is a little studied facet of European global expansion, from exploration to colonialism and beyond, and of the sovereign scientific orthodoxy that became established alongside it. The paper frames and discusses relevant details of this process over the longue durée, from pre-Linnaean taxonomies to current controversies over bioprospecting. Résumé: Cet article traite de certains aspects de l'histoire encore relativement négligée des plantes médicinales africaines. Le cœur de ce papier consiste en une discussion sous forme de tableau des plantes collectées en 1817 dans le royaume forestier d'Ashanti en Afrique de l'Ouest par Henry Tedlie, un membre de la célèbre mission anglaise dirigée par Thomas Bowdich. Plus généralement, cet article examine les différents épisodes de la collection de spécimens de plantes d'Akan, d'Ashanti et d'Afrique par les Européens, et la classification officielle de celles-ci dans une taxonomie botanique occidentale utilisée maintenant dans le monde entier. La cueillette de plantes au potentiel médicinal est une facette peu étudiée de l'expansion globale de l'Europe, allant de l'exploration à la colonisation voire au-delà, et de l'orthodoxie scientifique souveraine qui l'accompagne. Ce papier inscrit et discute les détails pertinents de ce processus dans la longue durée, des taxonomies pré-linnéennes jusqu'aux controverses actuelles sur la bioprospection.